The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1136/bmjresp-2014-000056
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of sepsis stage metabolic profiles with an LC/MS-MS-based metabolomics approach

Abstract: BackgroundTo identify metabolic biomarkers that can be used to differentiate sepsis from systemic inflammatory response syndrome (SIRS), assess severity and predict outcomes.Methods65 patients were involved in this study, including 35 patients with sepsis, 15 patients with SIRS and 15 normal patients. Small metabolites that were present in patient serum samples were measured by liquid chromatography mass spectrometry techniques and analysed using multivariate statistical methods.ResultsThe metabolic profiling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
57
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 34 publications
0
57
0
1
Order By: Relevance
“…Further analysis revealed that 2-phenylacetamide, dimethyllysine, glyceryl-phosphoryl-ethanolamine and D-cysteine could predict the severity of sepsis. Glyceryl-phosphoryl-ethanolamine is necessary for anticoagulation activity, and its altered expression level could be due to coagulation disorders and vascular endothelial dysfunction during severe sepsis 71 . It is necessary to validate these results in additional cohorts to determine their clinical utility.…”
Section: Metabolomicsmentioning
confidence: 99%
“…Further analysis revealed that 2-phenylacetamide, dimethyllysine, glyceryl-phosphoryl-ethanolamine and D-cysteine could predict the severity of sepsis. Glyceryl-phosphoryl-ethanolamine is necessary for anticoagulation activity, and its altered expression level could be due to coagulation disorders and vascular endothelial dysfunction during severe sepsis 71 . It is necessary to validate these results in additional cohorts to determine their clinical utility.…”
Section: Metabolomicsmentioning
confidence: 99%
“…There is relatively little metabolomics work in sepsis, but in one study, carnitine and sphingolipid metabolism were also modified during sepsis (1013), while in another (1014), a suite of molecules were decreased during acute sepsis. However, the patients involved here were quite close to death, so it is not clear that comparisons between the metabolome in PE and in dying patients are that worthwhile.…”
Section: Metabolomic Biomarkersmentioning
confidence: 99%
“…There is relatively little metabolomics work in sepsis, but in one study carnitine and sphingolipid metabolism were also modified during sepsis [946], while in another [947] a suite of molecules were decreased during acute sepsis. However, the patients involved here were quite close to death, so it is not clear that comparisons between the metabolome in PE and in dying patients are that worthwhile.…”
Section: Metabolomic Biomarkersmentioning
confidence: 99%